Exploration of Groups Through Latent Structural Model - Shamshad, Bushra; Siddiqi, Junaid Saghir (Journal of Basic & Applied Sciences, 2012)
In this paper Latent Class Analysis is applied on two different data sets. One of which is of elections of Karachi University Teacher Society (KUTS) in year 1993-1994. Members of two (Rightist and Mix) groups were competing for the post of President, Vice president, Secretary and Treasurer. The second data is about the study of parenting style on rearing children along with the factors self esteem and thoughts of suicide. From both the data set we will be able to come across the groups prevailing in our society and be able to assign conditional probability to individual, to which group they belong.